2013
DOI: 10.1371/journal.pone.0067373
|View full text |Cite
|
Sign up to set email alerts
|

Lin28 Mediates Radiation Resistance of Breast Cancer Cells via Regulation of Caspase, H2A.X and Let-7 Signaling

Abstract: Resistance to radiation therapy is a major obstacle for the effective treatment of cancers. Lin28 has been shown to contribute to breast tumorigenesis; however, the relationship between Lin28 and radioresistance remains unknown. In this study, we investigated the association of Lin28 with radiation resistance and identified the underlying mechanisms of action of Lin28 in human breast cancer cell lines. The results showed that the expression level of Lin28 was closely associated with resistance to radiation tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 20 publications
1
42
0
Order By: Relevance
“…On the contrary, a recent report showed correlation of increased expression of OCT4 and NANOG with cisplatin resistance in oral squamous cell carcinoma [52]. So far, there is a single study on LIN28, showing it could be a potential target for overcoming radiation resistance in breast cancer [57]. To the best of our knowledge, this is the first study evaluating the role of OCT4, NANOG, SOX2, and LIN28 genetic variants with breast cancer response to NACT.…”
Section: Discussionmentioning
confidence: 73%
“…On the contrary, a recent report showed correlation of increased expression of OCT4 and NANOG with cisplatin resistance in oral squamous cell carcinoma [52]. So far, there is a single study on LIN28, showing it could be a potential target for overcoming radiation resistance in breast cancer [57]. To the best of our knowledge, this is the first study evaluating the role of OCT4, NANOG, SOX2, and LIN28 genetic variants with breast cancer response to NACT.…”
Section: Discussionmentioning
confidence: 73%
“…While stable expression of Lin28 in cancer cells with low Lin 28 levels significantly reduced their sensitivity to paclitaxel, LIN28A knockdown in T47D cells effectively sensitized them to the drug. In another study, LIN28A was reported to be responsible for breast cancer cell resistance to radiation (Wang et al, 2013). Highest expression level of LIN28A was found in T47D cancer cells which were most resistant to radiation treatment.…”
Section: Lin28a/lin28b In Cscs Metastasis and Resistance To Chemothmentioning
confidence: 99%
“…Restoration of let-7a expression significantly resensitized cells to radiation treatment [69]. Wang et al found that miR-23b expression was down in radiation resistant lines of pancreatic cancer cells.…”
Section: Mirnas As Cancer Therapy Sensitizersmentioning
confidence: 99%